Effects of Expressive Arts–Based Interventions on Adults With Intellectual Disabilities: A Stratified Randomized Controlled Trial - Ho, Rainbow T. H.; Chan, Caitlin K. P.; Fong, Ted C. T.; Lee, Pandora H. T.; Lum, Derek S. Y.; Suen, S. H. (Frontiers in Psychology, 2020)
Background: The present study aimed to examine the effects of expressive arts–based intervention (EABI) on the behavioral and emotional well-being of adults with intellectual disabilities. Methods: This study assigned 109 Chinese adults with intellectual disabilities into EABI (N = 55) or control groups (N = 54) using stratified randomization. Pre- and post-intervention quantitative assessments were conducted of aberrant behaviors, personal well-being, mood and color usage in drawings. Focus group interviews were conducted at the post-intervention stage. Repeated-measures analysis of covariance evaluated the EABI effects with age, gender and degree of intellectual disability as covariates, and latent profile analysis examined the patterns of color usage in drawings. Qualitative thematic analysis was performed on the interview data. Results: The interview findings suggest that the EABI group was more emotionally expressive and stable after the intervention. Compared to the control group, the EABI group tended to use more diverse colors and leave less empty space in their drawings. No significant overall improvements were found in the EABI group with respect to aberrant behaviors, mood or personal well-being. Among males, the EABI participants showed significantly more anger and less energetic moods than those in the control group. Among females, the EABI participants showed significantly lower levels of aberrant behavior than those in the control group. Conclusions: The results of this study suggest that expressive arts–based interventions have different effects on the emotional and behavioral well-being of male and female participants. Moreover, increased color usage may imply a more positive state of emotional well-being.